PS-P08-4: FOXO3 LONGEVITY GENOTYPE ATTENUATES THE IMPACT OF HYPERTENSION ON RISK OF INTRACEREBRAL HEMORRHAGE. (January 2023) - Nakagawa, Kazuma; Randi, Chen; Greenberg, Steven M; Ross, G Webster; Willcox, Bradley J; Donlon, Timothy A; Allsopp, Richard C; Willcox, D Craig; Masaki, Kamal H; Morris, Brian J
Abstract : Objective: To determine the association between the longevity-associated G allele of FOXO3 SNP rs2802292 and risk of hypertension mediated intracerebral haemorrhage (ICH). Design: Prospective population-based longitudinal study. Methods: The cohort comprised Japanese American men living on Oahu, Hawaii, who were recruited from 1965 to 1968 for the Kuakini Honolulu Heart Program. Age adjusted incidence of ICH by hypertension status was assessed for the whole cohort after stratifying by FOXO3 genotype. Cox regression models, adjusted for age, cardiovascular risk factors, and FOXO3 and APOE genotypes, were utilized to determine the relative risk of effect of hypertension on ICH. All models were created for the whole cohort and stratified by FOXO3 G allele versus TT genotype. Results: Among 6, 469 men free of baseline stroke, FOXO3 G allele was present in 3, 009 (46.5%) participants. Overall, 183 subjects developed ICH over the 34 year follow-up period. Age adjusted ICH incidence rates were 0.90 and 1.32 per 1, 000 person years followup in those without and with hypertension, respectively (p = 0.002). After stratifying by FOXO3 genotype, this association was no longer significant in G allele carriers. In the whole cohort, hypertension was an independent predictor of ICH (RR = 1.70, 95%CI 1.25, 2.32; p = 0.0007). In stratified analyses, hypertension remained an independent predictor of ICH among the FOXO3 TT genotype group (RR = 2.02, 95% CI 1.33, 3.07; p = 0.001), but not in those who were carriers of the protective (G) allele of FOXO3 (RR = 1.39, 95% CI 0.88, 2.19; p = 0.15). Conclusions: The longevity associated FOXO3 G allele mitigates the impact of hypertension on ICH risk. Our finding has implications for risk assessment of patients with hypertension.